UJI VALIDITAS DAN RELIABILITAS KUESIONER THE 15-ITEM MYASTHENIA GRAVIS QUALITY OF LIFE SCALE VERSI BAHASA INDONESIA (MG-QOL15 INA) - Fitri Octaviana; Ahmad Yanuar Safri; Fikry Syahrial; Luh Ari Indrawati; Winnugroho Wiratman; Manfaluthy Hakim (NEURONA, 2020)
Introduction: Myasthenia gravis (MG) is a chronic autoimmune disease in the neuromuscular junction characterized with fluctuating weakness symptoms. Advance in the diagnosis and management of MG cases increases the patient’s life expectancy therefore the evaluation of therapeutic success is no longer based solely on coping with the symptoms, but also in evaluating the quality of life of patients. The 15-item Myasthenia Gravis Quality of Life scale (MG-QOL15) is a questionnaire utilized today to evaluate the quality of life of MG patients. Aims: To obtain a valid and reliable Indonesian version of MG-QOL15 instrument. Methods: Forty four MG patients at the Cipto Mangunkusumo Neurology outpatient clinic who met the inclusion criteria were included in this cross sectional study. Patients filled in the MG-QOL15 questionnaire twice at two days interval. The concept used for the validity test of MG-QOL15 INA is cross-cultural validation according to World Health Organization (WHO) method. Reliability test was assessed using Cronbach alpha value. Results: We performed WHO cross-cultural validation on MG-QOL15 INA and obtained Spearman correlation coefficient values ranging from 0.568-0.789 at the first examination and 0.574-0.763 at the retest. Cronbach’s alpha value at the first examination was 0.917 and 0.909 for the retest. Discussion: MG-QOL15 INA is valid and reliable to be used as an instrument in evaluating the quality of life of MG patients. Keywords: Myasthenia gravis, MG-QOL15, quality of life